INVESTIGATION OF HEALTH INSURANCE COSTS OF THE PATIENTS WITH MILD COVID-19 SYMPTOMS IN EMERGENCY ROOM - Durmus Ensar; Guneysu Fatih; Guner Gokhan Necip; Aslan Nuray; Yurumez Yusuf (Sanamed, 2021)
Introduction: This study aims to understand the burden of invoice costs of outpatients with mild Covid-19 symptoms on Social Security Institution (SSI); also, how it may have influenced the current economic situation.